False‐Negative Serologies in Amebic Liver Abscess: Report of Two Cases. Issue 2 (25th January 2013) - Otto, Marie‐Pierre; Gérôme, Patrick; Rapp, Christophe; Pavic, Michel; Vitry, Thierry; Crevon, Lionel; Debourdeau, Philippe; Simon, Fabrice
<x xml:space="preserve">Abstract</x> Amebiasis, the parasitic disease caused by Entamoeba histolytica, may result in extra‐intestinal diseases among which liver abscess is the most common manifestation. We report two cases of amebic liver abscess illustrating the inequal sensitivity of serologic tests detecting anti‐amebic antibodies.